Evaluation of a Novel Artificial Pancreas: Closed Loop Glycemic Control System With Continuous Blood Glucose Monitoring. Issue 4 (18th March 2013) - Tsukamoto, Yuuki; Kinoshita, Yoshihiko; Kitagawa, Hiroyuki; Munekage, Masaya; Munekage, Eri; Takezaki, Yuka; Yatabe, Tomoaki; Yamashita, Koichi; Yamazaki, Rie; Okabayashi, Takehiro; Tarumi, Masatoshi; Kobayashi, Masaki; et al.
Abstract A closed‐loop glycemic control system using an artificial pancreas has been applied with many clinical benefits in Japan since 1987. To update this system incorporating user‐friendly features, we developed a novel artificial pancreas (STG‐55). The purpose of this study was to evaluate STG‐55 for device usability, performance of blood glucose measurement, glycemic control characteristics in vivo in animal experiments, and evaluate its clinical feasibility. There are several features for usability improvement based on the design concepts, such as compactness, display monitor, batteries, guidance function, and reduction of the preparation time. All animal study data were compared with a clinically available artificial pancreas system in Japan (control device: STG‐22). We examined correlations of both blood glucose levels between two groups (STG‐55 vs. control) using Clarke's error grid analysis, and also compared mean glucose infusion rate (GIR) during glucose clamp. The results showed strong correlation in blood glucose concentrations (Pearson's product‐moment correlation coefficient: 0.97; n = 1636). Clarke's error grid analysis showed that 98.4% of the data fell in Zones A and B, which represent clinically accurate or benign errors, respectively. The difference in mean GIRs was less than 0.2 mg/kg/min, which was considered not significant. Clinical feasibility study demonstrated sufficient glycemic control maintaining target glucose range between 80 and 110 (mg/dL), and between 140 and 160 without any hypoglycemia. In conclusion, STG‐55 was a clinically acceptable artificial pancreas with improved interface and usability. A closed‐loop glycemic control system with STG‐55 would be a useful tool for surgical and critical patients in intensive care units, as well as diabetic patients.